Variation in responses to incretin therapy: Modifiable and non-modifiable factors - Austin, Gregory O.; Tomas, Alejandra (Frontiers in Molecular Biosciences, 2023)
Type 2 diabetes (T2D) and obesity have reached epidemic proportions. Incretin therapy is the second line of treatment for T2D, improving both blood glucose regulation and weight loss. Glucagon-like peptide-1 (GLP-1) and glucose-stimulated insulinotropic polypeptide (GIP) are the incretin hormones that provide the foundations for these drugs. While these therapies have been highly effective for some, the results are variable. Incretin therapies target the class B G protein-coupled receptors GLP-1R and GIPR, expressed mainly in the pancreas and the hypothalamus, while some therapeutical approaches include additional targeting of the related glucagon receptor (GCGR) in the liver. The proper functioning of these receptors is crucial for incretin therapy success and here we review several mechanisms at the cellular and molecular level that influence an individual’s response to incretin therapy.